Dracula under siege: Persistent demand for a threatened and range-restricted orchid taxa - Edicson Parra-Sánchez; Luis Baquero; Juan Camilo Ordóñez-Blanco; Karen Gil-Amaya; David P. Edwards; Oscar Morton (Biological Conservation, 2026)

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Spatial extent predicts Andean epiphyte biodiversity responses to habitat loss and fragmentation across human‐modified landscapes - Edicson Parra‐Sanchez; David P. Edwards (Journal of Biogeography, 2024)
Aim Human‐driven landscape processes such as habitat loss and fragmentation act on biodiversity, but their effects are mediated by the spatial scale at which they are observed. We aim to analyse the scale‐of‐effects (direction and spatial extent) of landscape‐scale processes that best explain species richness and abundance across epiphyte communities. Location Neotropics, Northern Andes, Colombia, Eastern cordillera. Taxon Vascular epiphytes, Orchidaceae. Methods We used field data to unravel the scale‐of‐effect of three landscape processes—habitat loss (forest cover), fragmentation (number of patches) and edge effects (edge density)—on epiphyte biodiversity. Vascular epiphytes were sampled in the understorey across 141 plots within 23 Andean forests in the eastern Colombian cordillera We focused on the community‐level responses (species richness and total abundance) of the hyperdiverse vascular epiphyte communities using generalized linear mixed models to quantify the direction and the spatial extent of the scale‐of‐effects. Results Habitat loss and edge effects act at fine spatial extents (scale‐of‐effects = 200 m), predicting low species richness and abundance across groups. Likewise, fragmentation negatively impacts communities, but operates at larger spatial extents (scale‐of‐effects = 2000–2400 m radius). The detection of these effects is contingent upon the spatial extent and specific landscape processes involved. Models of habitat loss within a spatial extent of 800–1500 m (large confidence intervals), fragmentation below 300 m, and edge effects above 800 m show weak statistical support (marginal r 2 = 0.02–0.1). Thus, the impacts of these landscape processes may be overlooked if studied at inadequate spatial extents. Main Conclusions We showed that habitat loss, fragmentation and edge effects all play a negative role on understorey epiphytic communities, but their detectability is scale dependant. The scale‐of‐effects can assist landscape designs that are beneficial for epiphytic communities, by preserving forest cover, and reducing fragmentation and exposure to edge effects at small scales (200–300 m). Conversely, landscape‐scale actions directed at reducing habitat loss and fragmentation function at larger spatial extents (>2000 m). Selecting a priori or inadequate spatial extents of analysis can obscure the detectability of landscape processes.

Transformation of natural habitat disrupts biogeographical patterns of orchid diversity - Edicson Parra-Sanchez; Robert P. Freckleton; Matthew G. Hethcoat; Jose Manuel Ochoa-Quintero; David P. Edwards (Biological Conservation, 2024)

Avian biodiversity losses from grazing of high Andean páramo - Simon C. Mills; Edicson Parra Sanchez; Jacob B. Socolar; Chris Bousfield; Bryn Coffey; Jos Barlow; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; David P. Edwards (Biological Conservation, 2023)

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.